The relationship between energy intake with stunting and wasting among toddlers in Aertembaga subdistrict, Bitung city - Punuh, Maureen I.; Akili, Rahayu H.; Tucunan, Ardiansa (International Journal Of Community Medicine And Public Health, 2024)
Background: Stunting and wasting are forms of malnutrition that can occur in toddlers. Stunting and wasting can increase the risk of physical and cognitive growth retardation. One of the factors directly causing stunting and wasting is energy intake. The purpose of this study was to determine the relationship between energy intake with stunting and wasting in toddlers. Methods: This study was a type of quantitative research with an analytical survey method using a cross-sectional design conducted in Aertembaga district, Bitung city. The sample taken was 205 respondents using purposive sampling technique and met the inclusion and exclusion criteria. Data were analyzed univariately and bivariately using the chi square statistical test. Results: The percentage of stunted toddlers was 45.9%, not stunted was 54.1%. The percentage of toddlers with wasting was 8.3% and not wasting was 91.7%. Energy intake of toddlers in the sufficient category amounted to 35.6%, the less category amounted to 33.2% and the more category amounted to 31.2%. Conclusions: There was an association between energy intake and stunting (p=0.005) and wasting (p=0.037) in toddlers. Optimization of stunting and wasting prevention programs is needed to reduce stunting and wasting rates among under-fives in Aertembaga sub-district, Bitung city.